2021
DOI: 10.1155/2021/3554219
|View full text |Cite
|
Sign up to set email alerts
|

MiR-466 Inhibits the Progression of Severe Hepatocellular Carcinoma via Regulating FMNL2-Mediated Activation of NF-κB and Wnt/β-Catenin Pathways

Abstract: Hepatocellular carcinoma (HCC) has threatened the health of humans, and some evidence has indicated that miR-466 involves the progressions of some cancers. This study focused on the role of miR-466 in the formation and development of HCC. The expression levels of miR-466 in the tissues of patients and HCC cell lines were measured by qRT-PCR, and CCK-8, transwell assay, and flow cytometry assay were used to observe the functions of miR-466 on the HCC cells. Moreover, the miRNA databases, dual-luciferase reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
(27 reference statements)
1
4
0
Order By: Relevance
“…It has been found that FBXW7 serves as an inhibitor to suppress the activation of Wnt pathway in lung cancer [11]. Hence, this study sustains that attenuated miR-211-5p can promote the injury and apoptosis of myocardial cells suffering I/R via regulating FBXW7 mediated the inactivation of Wnt pathway [12].…”
Section: Introductionsupporting
confidence: 75%
“…It has been found that FBXW7 serves as an inhibitor to suppress the activation of Wnt pathway in lung cancer [11]. Hence, this study sustains that attenuated miR-211-5p can promote the injury and apoptosis of myocardial cells suffering I/R via regulating FBXW7 mediated the inactivation of Wnt pathway [12].…”
Section: Introductionsupporting
confidence: 75%
“…At molecular level, miRNA-466 decreases FMNL2 expression to inhibit β-catenin signaling. 179 Notably, miRNA/β-catenin axis can also be affected by anti-tumor agents. A recent has revealed anti-tumor activity of astragaloside IV in HCC therapy.…”
Section: Beta-catenin and Hepatocellular Carcinomamentioning
confidence: 99%
“…109 miRNA-466 exerts its inhibitory effects on HCC progression by regulating formin-like 2 (FMNL2)-mediated activation of WNT/β-catenin signaling. 110 Indirect inhibitory effects on the WNT/β-catenin pathway impairing HCC growth and metastasis have been demonstrated for miRNA-26 b, miRNA-342, and miRNA-186. miRNA26b inhibits the expression of zinc ribbon domain-containing 1 (ZNRD1).…”
Section: Non-coding Rnas Affecting Wnt/β-catenin Signaling In Hccmentioning
confidence: 99%